2013
DOI: 10.1103/physrevd.87.125002
|View full text |Cite
|
Sign up to set email alerts
|

Chiral symmetry breaking in the pseudo-quantum electrodynamics

Abstract: In this work, we study the chiral symmetry breaking in pseudo-quantum electrodynamics in (2 þ 1) dimensions, which is designed to reproduce a Coulomb potential for charged particles on a plane interacting via photons propagating in (3 þ 1) space-time dimensions and would be relevant for applications to condensed-matter systems. Using an ultraviolet cutoff in the momentum integrals, we show that there is a critical dimensionless coupling c ¼ =4 above which there is chiral symmetry breaking. In the case of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 72 publications
(102 reference statements)
4
71
0
Order By: Relevance
“…This non-local gauge theory is similar to the one studied in Ref. [43], where the authors also showed the breaking of chiral symmetry. By adding the contribution of the long-range interaction to Σ(p) and following a standard procedure, we obtain a differential equation similar to Eq.…”
Section: B Long-range Interactionsupporting
confidence: 81%
See 1 more Smart Citation
“…This non-local gauge theory is similar to the one studied in Ref. [43], where the authors also showed the breaking of chiral symmetry. By adding the contribution of the long-range interaction to Σ(p) and following a standard procedure, we obtain a differential equation similar to Eq.…”
Section: B Long-range Interactionsupporting
confidence: 81%
“…These kind of interactions have been already studied separately in the context of dynamical mass generation in Refs. [40][41][42][43]. This mechanism is relevant in interacting quantum-field theories and is related to the dynamical breaking of a classical symmetry due to quantum effects.…”
Section: Dynamical Gap Generationmentioning
confidence: 99%
“…In spite of the fact that we are using 2-component Dirac spinors, however, we do not break TRS ab initio because we are summing over the two species (as we may infer from the physical value of N f ). An SU(4) version of this model has been recently used to study dynamical gap generation and chiral symmetry breaking in graphene [29].…”
Section: Modelmentioning
confidence: 99%
“…(1) dynamically generates a gap in the SU(4) case due to a breaking of the chiral symmetry [29]. Here, we investigate the SU(2) case and show that an infinite sequence of discrete energy eigenstates is dynamically generated.…”
mentioning
confidence: 99%
“…In the dynamical description, it is expected to generate a set of quantized-energy levels in graphene as well as an interaction driven quantum valley Hall effect [17] at low enough temperatures. Furthermore, chiral-symmetry breaking has been shown to take place for both zero and finite temperatures [18,19]. It also occurs in the presence of a Gross-Neveu interaction, whose main effect is to decrease the critical coupling constant, yielding a better scenario for dynamical mass generation [20].…”
Section: Introductionmentioning
confidence: 99%